2020
DOI: 10.2139/ssrn.3593732
|View full text |Cite
|
Sign up to set email alerts
|

Horizontal Cooperation on Investment: Evidence From Mobile Network Sharing

Abstract: We present a structural model to investigate the effects of horizontal cooperation on investment in the context of telecommunication networks. More specifically, we estimate the effect of network sharing in the mobile telecommunications industry on prices, network quality and consumer welfare. The presented framework allows estimating the effects of different types of sharing agreements including common ownership of shared assets in a joint venture company or collaboration via geographical separation (geo-spli… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 20 publications
(29 reference statements)
0
1
0
Order By: Relevance
“…Anyway, empirical studies do not seem to highlight this point. Cojoc et al (2020) present a structural model of the Ran sharing agreement in the Czech Republic between the two leading operators in the market. They found that the cost savings are passed on to consumers who benefit from lower prices and a higher download speed.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Anyway, empirical studies do not seem to highlight this point. Cojoc et al (2020) present a structural model of the Ran sharing agreement in the Czech Republic between the two leading operators in the market. They found that the cost savings are passed on to consumers who benefit from lower prices and a higher download speed.…”
Section: Literature Reviewmentioning
confidence: 99%
“…However, if the impact of investment quality is more homogeneous (i.e., the "loyalty" parameter is prices. In a companion paper, Cojoc et al (2020) set up a structural model that indicates that network sharing benefits consumers through lower prices as well as higher quality (measured by download speed). close to zero), it may be preferable for both consumers and economic welfare to ban any cooperation, i.e., network sharing should be prohibited altogether.…”
Section: Introductionmentioning
confidence: 99%